Adaptive constellations of protective marks: eyespots, eye stripes and diversion of attacks by fish. (January 2016) - Kjernsmo, Karin; Grönholm, Miranda; Merilaita, Sami
Abstract : Coloration of animals often includes spectacular markings that supposedly decrease predation risk. Many vertebrates have eye stripes that have been suggested to conceal the noticeable shape of the eye from predators. Another salient mark in a wide range of taxa that sometimes co-occurs with an eye stripe is the eyespot. Some eyespots divert strikes of attacking predators, but whether the eyelike appearance is essential for the divertive effect is not known. Although numerous species of fish provide iconic examples of spectacular coloration, experimental studies on the protective function of coloration against fish predators are scarce. We investigated the divertive potential of prey marks, using artificial prey and three-spined sticklebacks, Gasterosteus aculeatus, as a model for predator perception and behaviour. A significant proportion of attacking fish directed their strike towards an eyespot, but when compared to a square-shaped mark, the bias was not significantly stronger. Importantly, a stripe running through the eyelike mark strongly influenced the attacking fish. When presented simultaneously, the fish directed their strikes towards an intact eyelike shape and away from an eyelike shape disrupted by a stripe. Our results demonstrate that marks of different shapes differ in their divertive potential, and this may contribute to the wide occurrence of eyespots in prey. Importantly, they also show that a stripe can effectively decrease the salience of an eyelike pattern, which provides the first experimental evidence for the adaptive benefit for eye stripes. Moreover, the joint effect of the eyespot and the disruptive eye stripe indicates that prey marks with different functions can form adaptive constellations to manipulate the attack behaviour of predators. Highlights: We studied the innate response of attacking fish towards eyespots and eye stripes. An eyespot diverted predator strikes, but another mark could cancel out this effect. Fish struck towards an eyespot and away from an eyelike mark disrupted by a stripe. An eye stripe conceals the eye, increasing the divertive effect of an eyespot nearby. These results can explain the co-occurrence of eye stripes and eyespots in many fish.